Tricho-dento-osseous syndrome: a brief review for dentistry - Ricardo Barbosa Lima; Taigor Alves Azevedo; Amanda Lopes; Aquiles Sales Craveiro Sarmento; Carlos Eduardo Palanch Repeke (Universidade Federal do Rio Grande do Sul. Faculdade de Odontologia, 2020)
Introduction: Tricho-dento-osseous syndrome is a ultra-rare ectodermal dysplasia related to genetic alterations in the DLX3 gene of interest to the health sciences due to its clinical manifestations. Aim: To synthesize the scientific evidence about tricho-dento-osseous syndrome, especially for dentistry. Methods: A bibliographic search was performed in the MEDLINE / PubMed, Web of Science and Scopus databases. A search strategy with descriptors was applied to all databases mentioned to reach scientific articles. The articles reached in all databases had their titles and abstracts read in search of adaptation to the proposed objective. There was no restriction on the year of publication, country or language. Literature review: Patients diagnosed with this syndrome have dental enamel defects and severe taurodontism, especially in the permanently lower first molars. In addition to these signs, other manifestations may be associated, such as curly hair, increased bone density and changes in craniofacial bones. The diagnosis of tricho-dento-osseous syndrome can be challenging due to the heterogeneity and wide phenotypic variation presented by patients with DLX3 mutations, since this gene is associated with several functions, especially related to cell differentiation and biomineralization. In addition, it is necessary to consider that other dental anomalies may be confused with tricho-dento-osseous syndrome, especially cases of imperfect amelogenesis associated with taurodontism. Conclusion: For dentistry, oral manifestations caused by this syndrome become relevant for diagnostic and therapeutic purposes, although there are no clinical protocols for dental management of this patients.